New results of paleomagnetic studies of red-colored Silurian deposits - E. Polyachenko; V. Bakhmutov; L. Konstantinenko; M. Teyser-Elenska; M. Kadzyalko-Hofmokl'; T. Scarboviychuk; V. Yakukhno (Геофизический журнал, 2014)
New results of paleomagnetic studies of red-colored rocks of the Late Silurian of southwestern Ukraine (Podolian area, the Dniester river basin) have been presented. Sedimentary unit of red-colored deposits as a part of upperconovsk subsuite of Malinovets series are represented by dolomites comparable with Ludford stage of the International geological scale, and was studied in two sections. The distinguished medium-temperature component of magnetization (O = 53,4 °S, A = 5,9 °E) corresponds to the direction of the Permian poles TCMP for the Baltic area that indicates magnetization reversal of rocks. High temperature (characteristic) component of magnetization distinguished on lots of samples of the Konovsk suite corresponds to the Silurian fragment of TCMP for the Baltic and is determined by the presence of terrigenous hematite (ti-tanomagnetite) grains and is, according to our interpretation, the primary magnetization. Its corresponding paleomagnetic pole (O = 19,9 °S, A = 339,8 °E) is in good agreement with the Silurian fragment of TCMP. The results are in good accordance with the previous measurements for grey-colored sedimentary rocks of the Silurian from Podolia.